Case-Based Evidence for Screening Pornography in Marital Therapy. Issue 3 (July 2021) - Sharma, Manoj Kumar; Anand, Nitin; Sunil, Shweta; Tadpatrikar, Ashwini; Vishwakarma, Akash; Thakur, Pranjali Chakraborty; Singh, Priya; Ajith S.J.,; John, Nisha; Sahu, Maya; Mondal, Ishita; Suma N.,; et al.
Pornography has become a modality to experience sexual expression. It is used in a recreational manner to enhance sexual life. However, in some cases, excessive usage can lead to distress in the other partner. In this case, the client sought help at the specialty clinic for management of pornography use. A clinical interview was used to get details of the patterns of porn use and dysfunctions caused by the same. Beck's Depression Inventory was used for the assessment of associated depression. The results highlight the presence of distress in the female partner due to excessive pornography consumption in the other partner. This report has implications for developing sensitization and intervention program to address these issues within the marital context.